Distal Basilar Artery "Umbrella Aneurysm" Treated by Radial Artery Graft Bypass From the External Carotid Artery to Posterior Cerebral Artery and Clip Trapping: 2-Dimensional Operative Video. Issue 3 (25th June 2021) - Shenoy, Varadaraya S; Lavergne, Pascal; Qazi, Zeeshan; Ghodke, Basavaraj V; Sekhar, Laligam N
Abstract: A 71-yr-old woman was discovered to have an incidental distal basilar artery (BA) fusiform aneurysm 7 × 5 mm in dimension, shaped like an "umbrella handle" with critical stenosis distal to the aneurysm. The right posterior cerebral artery (PCA) P1 segment was small; the left posterior communicating artery (PComA) was miniscule. Because the natural history of fusiform BA aneurysms is poorly defined, this was equated to a saccular aneurysm, with an estimated 10-yr rupture rate of 29%. 1-8 After discussion of alternative treatments, the patient decided upon surgery. Because of inadequate collateral circulation, a bypass to the left PCA was deemed necessary. The aneurysm was exposed by an extended trans-sylvian approach, and the left PCA P2 segment was visualized subtemporally. The left radial artery (RAG) was extracted, and pressure distended to prevent vasospasm. The RAG bypass was sutured first to the P2, and then to the cervical external carotid artery (ECA); the BA aneurysm was then clipped. The proximal anastomosis of the bypass needed revision because of poor flow; a 4-mm punch hole was made to widen the arteriotomy on the ECA. The patient was discharged home with mild memory loss and partial left cranial nerve III palsy. After discharge, she developed a severe left hemicrania, resolved with gabapentin. At 6-wk follow-up, she was asymptomatic, and computed tomography (CT) angiogram demonstrated patency of the bypass. The patient gave informed consent for surgery and video recording. All relevant patient identifiers have been removed from the video and accompanying radiology slides.